'A vision of paradise lost': coaching as a grasshopper rather than an ant. Issue 1 (2nd January 2022) - Burke, Michael
ABSTRACT: The work of Bernard Suits continues to be discussed in the sports philosophy field, over forty years after the publication of his brilliant book, The Grasshopper: Games, Life, and Utopia . Much of this discussion has looked at how the perfectionist consequences of Suits' definition of game playing impacts on gamewrighting. However, it is not just the cheat, the trifler, the spoilsport, or even the subperfectionist that the gamewrighter must be concerned with. This paper uses the spirit of the Grasshopper to suggest that what we should also be concerned about in contemporary sport at almost all levels, and what gamewrighting discussions should focus on, is the loss of player autonomy because of the control exerted by coaches, managers and analysts.